The Assessment of Oropharyngeal Dysphagia in Adults - Frederick Y. Hawson (Philippine Journal of Otolaryngology Head and Neck Surgery, 2009)
One of the more important and critical referrals that otolaryngologists can receive from colleagues in internal medicine, family medicine and geriatrics is the assessment of swallowing problems or dysphagia of their patients.